2019
DOI: 10.1021/acsaelm.8b00091
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interfacial Toughness in a Novel “GaN-on-Diamond” Material for High-Power RF Devices

Abstract: GaN thin film integrated to polycrystalline diamond substrates is a novel microwave transistor material with significantly improved heat dissipation capability. Due to the thermal and mechanical properties mismatch between GaN and diamond, a natural concern arises in terms of its interfacial stability as currently there is no established method to evaluate the interfacial toughness in GaN-ondiamond material. Using three generations of "GaN-on-Diamond" materials with varying process parameters, a comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 69 publications
(206 reference statements)
0
10
0
Order By: Relevance
“…The test has already been used by a number of groups to study hard, thin, and well‐adhering coatings . More detail on the method are described in Nakao et al In addition, the nanoindentation method is also a very common quantitative, semi‐quantitative method for measuring the adhesion energy properties of coating/substrate materials, such as Dong Liu and Q. Zhou et al The change of acoustic signal for brittle diamond film on the GaN substrate reflects this adhesion, as shown in Figure . The acoustic signal shows that the critical load of the GaN‐SiN‐Diamond sample is 14 N. While the critical load of the GaN‐AlN‐Diamond sample is only about 6 N. The results shows that the diamond film on the GaN with the AlN dielectric layer has a lower adhesion compared with the sample with the SiN dielectric layer and proper selection of the dielectric layer can improve the adhesion of the film .…”
Section: Resultsmentioning
confidence: 99%
“…The test has already been used by a number of groups to study hard, thin, and well‐adhering coatings . More detail on the method are described in Nakao et al In addition, the nanoindentation method is also a very common quantitative, semi‐quantitative method for measuring the adhesion energy properties of coating/substrate materials, such as Dong Liu and Q. Zhou et al The change of acoustic signal for brittle diamond film on the GaN substrate reflects this adhesion, as shown in Figure . The acoustic signal shows that the critical load of the GaN‐SiN‐Diamond sample is 14 N. While the critical load of the GaN‐AlN‐Diamond sample is only about 6 N. The results shows that the diamond film on the GaN with the AlN dielectric layer has a lower adhesion compared with the sample with the SiN dielectric layer and proper selection of the dielectric layer can improve the adhesion of the film .…”
Section: Resultsmentioning
confidence: 99%
“…A more detailed description and discussion of the main findings is included in Section 4.1. The mechanical and thermo-mechanical integrity of the diamond/GaN interface, which impacts profoundly the reliability of the devices, was also addressed [97][98][99]. As a general finding, Liu et al concluded that the GaN/diamond interface has a high mechanical stability, showing the potential of this material system for the fabrication of reliable devices [97].…”
Section: Gan-on-diamondmentioning
confidence: 99%
“…As an example, for a particular GaN-on-diamond HEMT, the reduction in the TBR GaN/diamond related with the SiN layer from 13 to 3 m 2 •K/GW would reduce the total R th of the device from 2.8 to 1.9 K•mm/W, which corresponds to a 35% decrease in the peak operating temperature rise at a given power level [73]. However, one should also keep in mind that, despite smoother GaN/SiN/diamond interfaces lead to lower TBR GaN/diamond , they also show reduced interfacial fracture toughness, in comparison with rougher interfaces [99], which could negatively impact the devices reliability.…”
Section: Decreasing Thermal Stressmentioning
confidence: 99%
“…The use of III-nitride (III-N) semiconductor materials for various energy-efficient optoelectronic and electronic devices has been extensively investigated due to III-N’s wide energy band gap, high critical electrical field, and good thermal stability. GaN p–i–n diode is a fundamental and important device for a number of applications, such as rectifiers, photodetectors (PDs), microwave switches, solar cells, and so on. There has been tremendous progress in recent years on thin film-based GaN p–i–n diodes on native GaN substrates and foreign substrates. Despite outstanding device performance obtained for GaN p–i–n diodes grown on native GaN substrates, bulk GaN substrates with low-defect density are still expensive and only available in small sizes, limiting their use for volume productions. GaN p–i–n diodes grown on foreign substrates, such as Si and sapphire, show dislocation density in the range of 10 6 –10 9 /cm 2 , depending on the lattice constant mismatch level, thin film thickness, and growth methods. ,, Wide energy band gap III-N materials are also promising for monitoring and detecting signals in high-temperature environments, , such as furnaces, combustion chambers, and so on.…”
Section: Introductionmentioning
confidence: 99%